THE PERCEPTION ON THE CONTRIBUTION OF ISLAMIC BANKS AND ISLAMIC WINDOWS TOWARDS THE GROWTH OF NIGERIAN ECONOMY - Jibril Musa Talba; Ibrahim Mohammed Lawal; Umar Babagana Imam (Journal of Islamic Monetary Economics and Finance, 2019)
This study was to assess the perception on the contribution of Islamic banks and Islamic windows towards the growth of the Nigerian economy. To document this, data were obtained through the use of structured questionnaires. 379 copies of questionnaires were administered based on the sample size obtained via the use of Taro Yamane formula. 367 questionnaires were successfully retrieved. Variables such as deposit activities, loan activities and perception of bank employees were also adopted as explanatory or independent variable and dependent variable respectively. To support the study hypothesis were also formulated. For the analysis, measures of central tendency (tables, frequency and percentages) and inferential statistics (Logit Regression) were used. The result revealed that the variables (i.e. deposit and loan activities) have a positive impact on the growth of Nigeria’s economy because the probability values of the variables (P=0.003 and 0.019) were less than alpha (α =0.05) level of significance. In other words, this implies that Islamic banks and windows have largely supported private consumption, business investments of its customers, aid government spending via sukuk to fund developmental projects of its customers. The study concludes that Islamic banks and windows have contributed towards the growth of the Nigeria’s economy. Furthermore, the study recommends that there is need for creating the necessary legal framework to ensure its smooth operations, intensify efforts on creating public awareness, rolling out more shariah compliant products that can take care of the peculiarities that exist in business environment and training and retraining of staff on effective Islamic banking.